2002
DOI: 10.1063/1.1472506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of small-scale turbulent motions on the filtered velocity gradient tensor as deduced from holographic particle image velocimetry measurements

Abstract: The effects of small-scale motions on the inertial range structure of turbulence are investigated by considering the dynamics of the velocity gradient tensor (Ãij) filtered at scale Δ. In addition to self-interactions and the filtered pressure Hessian, the evolution of Ãij is determined by the subgrid-scale stress tensor. As in the so-called restricted Euler dynamics, the evolution equations can be simplified by considering the invariants RΔ and QΔ of Ãij. The effects of the subgrid-scale stress tensor on RΔ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 28 publications
10
74
0
Order By: Relevance
“…Note that this tendency might be moderated somewhat by the small-scale stress terms which we have neglected in (2.40); cf. Van der Bos et al (2002).…”
Section: The Strongly Uv-local Termsmentioning
confidence: 99%
“…Note that this tendency might be moderated somewhat by the small-scale stress terms which we have neglected in (2.40); cf. Van der Bos et al (2002).…”
Section: The Strongly Uv-local Termsmentioning
confidence: 99%
“…Subsequent experiments in a turbulent jet, 31 a cylinder wake, 32,33 and a square duct 34,35 have revealed further statistical information on the geometry, alignment tendencies, and intermittency of the SGS turbulence. Further, O'Neil and Meneveau 32 showed that large-scale organised structures within a turbulent free shear flow are shown to have a significant impact on the statistical distribution of SGS TKE dissipation, even at filter scales well inside the inertial range.…”
Section: Introductionmentioning
confidence: 99%
“…Further, O'Neil and Meneveau 32 showed that large-scale organised structures within a turbulent free shear flow are shown to have a significant impact on the statistical distribution of SGS TKE dissipation, even at filter scales well inside the inertial range. van der Bos et al 34 examined the effect of the smallest (SGS) scales on the inertial range structures of turbulence using holographic particle image velocimetry (PIV) in a turbulent square duct flow, away from the wall. The separation of scales was achieved by spatially filtering the data with a box filter of size 30 Kolmogorov (dissipative) length scales.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent experiments in a turbulent jet, 31 a cylinder wake, 32,33 and a square duct 34,35 have revealed further statistical information on the geometry, alignment tendencies, and intermittency of the SGS turbulence. Further, O'Neil and Meneveau 32 showed that large-scale organised structures within a turbulent free shear flow are shown to have a significant impact on the statistical distribution of SGS TKE dissipation, even at filter scales well inside the inertial range.…”
Section: Introductionmentioning
confidence: 99%